Evolution of the multilateral solution in the field of international environmental law and sustainable development (International relations and international law Journal, 2016)
The complex challenge of sustainable development is due the peculiarities of contemporary environmental issues and practical concern in the future of international law regulating the sphere of environmental protection. In its turn, the evolution of multilateral solutions to in the field of environment and sustainable development is linked with the problem of coordination and implementation of international standards into national law. Kazakhstan is an active member of the post-Copenhagen process, brings its own international initiatives within the process Rio. The most important is the trans-regional Partnership program “Green Bridge”.
Keywords: sustainable development; international environmental law; multilateral solutions to the Rio process; Kazakhstan’s initiative “Green Bridge”